Gambaran Tingkat Pengetahuan, Sikap Dan Tindakan Masyarakat Dalam Pemanfaatan Tanaman Obat Keluarga (TOGA) Di Kelurahan Sungai Lulut Kecamatan Sungai Tabuk - Haikal Rafi Maulana; Nazhipah Isnani; Nabila Hadiah Akbar; Muliyani Muliyani (UPPM Politeknik Unggulan Kalimantan, 2023)
TOGA is an abbreviation of family medicinal plants (TOGA). In essence, a toga is a piece of land, either in the yard, garden, or field, which is used to cultivate medicinal plants. The goal is to meet the family's medical needs. The existence of family medicinal plants in the home environment is very important, especially for families who do not have easy access to medical services. Understanding the benefits and efficacy of plant species to be safe, natural medicinal plants. The ancient Greeks who triumphed in 800 BC have also used about 63 species of medicinal plants using 657 types of plants. This study aims to describe the level of knowledge, attitudes and actions in the use of family medicinal plants (TOGA) in Sungai Lulut Village, Sungai Tabuk District. This research method uses a descriptive survey with accidental sampling technique, the population in this study are people who live in Sungai Lulut Village, Sungai Tabuk District, amounting to 1,002 people and getting a sample of 111 people. The results of this study indicate the level of knowledge of respondents about the use of TOGA in the category of good knowledge level as many as 29 respondents (26.12%), the level of attitude in the good category as many as 83 respondents (74.77%) and the level of action in the good category as many as 53 respondents (47 ,70%). The conclusion of this study is that the overall level of community knowledge about the use of TOGA plants is quite good (61.71%), the level of community attitude as a whole is good (82.21%) and the level of community action as a whole is quite good (69.90%)